Humanitarian accountability, bureaucracy, and self‐regulation: the view from the archive. Issue 2 (October 2015) - Roddy, Sarah; Strange, Julie‐Marie; Taithe, Bertrand
<x xml:space="preserve">Abstract</x> This paper contains a systematic exploration of local and national archives and sources relevant to charities and humanitarian fund appeals of the late Victorian and Edwardian eras (1870–1912) in Great Britain. It shows that the charitable world and humanitarian work share the same matrix and originate from the same roots, with considerable overlap between fundraising for domestic charity and overseas relief. These campaigns engaged in crucial self‐regulatory processes very early on that involved concepts such as formal accountability and the close monitoring of delivery. Far from lagging behind in terms of formal practices of auditing and accounts, charities and humanitarian funds often were in the pioneering group as compared with mainstream businesses of the period. The charitable sector, notably through the Charity Organisation Society in cooperation with the press, developed and delivered accountability and monitoring, while the state and the Charity Commission played a negligible role in this process.